THERMODYNAMIC PROPERTIES AND STABILITY OF ALF-BEARING TITANITE CATIOSIO4-CAALFSIO4 - Troitzsch U.; Ellis D.J. (My University, 2002)
Calorimetric and experimental data on AlF-bearing titanite are presented that yield thermodynamic properties of CaAlFSiO4, as well as activity-composition relations of binary titanite CaTiOSiO4–CaAlFSiO4. The heat capacity of synthetic CaAlFSiO4 was measured with differential scanning calorimetry between 170 and 850 K: C P =689.96–0.38647T+2911300T –2–8356.1T –0.5+0.00016179T 2 . Based on low-temperature heat capacity calculations with lattice vibrational theory (Debye model), the calorimetric entropy of CaAlFSiO4 can be expected to lie between 104.7 and 118.1 J mol–1 K–1. The temperature of the P21/a to A2/a phase change was determined calorimetrically for a titanite with X Al=0.09 (Ttransition =390 K). The decrease of the transition temperature at a rate of about 11 K per mol% CaAlFSiO4 is in good agreement with previous TEM investigations. The displacement of the reaction anorthite + fluorite = CaAlFSiO4 in the presence of CaTiOSiO4 was studied with high P–T experiments. Titanite behaves as a non-ideal, symmetrical solid-solution. The thermodynamic properties of CaAlFSiO4 consistent with a multi-site mixing model.